Implementasi Metode Analytical Network Process Dalam Rekrutmen Pegawai Pada Kantor Urusan Agama - M Fakhriza; Adnan Buyung Nasution; Muzaddidah, Cahaya Caya (Teknik Informatika Fakultas Ilmu Komputer, 2025)
Recruitment and selection of human resources is an important process in organizational management. Advances in information technology have brought significant changes in the way companies carry out recruitment and selection. Good employee performance appraisal is also an important factor in organizational development. To improve the quality of employees, the Office of Religious Affairs needs to carry out an appropriate recruitment process. In this context, the research will discuss the application of the Analytical Network Process (ANP) method in the KUA employee recruitment decision support system. By implementing the ANP method, it is hoped that agencies can speed up the recruitment process by selecting employees more objectively and in accordance with specified criteria.